Ghanaian farmers are using AICCRA-Ghana advisories to improve their climate-sensitive decision making - Ghana Outcome Impact Case Report (OICR for PDO 2) - Dalaa, Mustapha Alasan; Tepa-Yotto, Ghislain; Yeboah, Stephen (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Ghanaian farmers are using AICCRA-Ghana advisories to improve their climate-sensitive decision making.